Срочно!!! [latex] \frac{a+3}{ a^{2}-1 } - \frac{1}{ a^{2}+a }[/latex] [latex] \frac{a+4}{ a^{2}-2a } - \frac{a}{ a^{2}-4 } [/latex]
Срочно!!! [latex] \frac{a+3}{ a^{2}-1 } - \frac{1}{ a^{2}+a }[/latex]
[latex] \frac{a+4}{ a^{2}-2a } - \frac{a}{ a^{2}-4 }
[/latex]
Ответ(ы) на вопрос:
а+3 1 (а+3)а - (а-1)*1 а²+3а-а+1 а²+2а+1
--------------- - ----------- = ----------------------- = ---------------- = ---------------- =
(а-1)(а+1) а(а+1) а(а-1)(а+1) а(а-1)(а+1) а(а-1)(а+1)
(а+1)² а+1
--------------- = ----------
а(а-1)(а+1) а(а-1)
а+4 а (а+4)(а+2)-а*а а²+4а+2а+8-а² 6а+8
---------- - --------------- = --------------------- = -------------------- = ------------------ =
а(а-2) (а-2)(а+2) а(а-2)(а+2) а(а-2)(а+2) а(а-2)(а+2)
2(3а+4)
= ------------
а(а-2)(а+2)
Не нашли ответ?
Похожие вопросы